Prevalence of perceived cognitive dysfunction in survivors of a wide range of cancers: results from the 2010 LIVESTRONG survey - Schmidt, John E. (J Cancer Surviv, 2015)
PURPOSE: With cancer survivors now numbering over 13 million in the United States, and expected to continue to increase, it is important to consider the needs of this growing population. In the literature, one of the most common complaints by cancer survivors is perceived cognitive dysfunction. Since the preponderance of the research has focused on breast cancer survivors, the purpose of the present study was to explore the prevalence and correlates of perceived cognitive dysfunction in a large sample of cancer survivors with representation across a wide range of different types of cancer. METHODS: A sample of 3108 post-treatment cancer survivors completed the 2010 LIVESTRONG survey as part of a larger study of cancer survivorship. Respondents completed standardized questions regarding current and past perceived cognitive dysfunction, as well as depressive symptoms, and demographic and medical variables. RESULTS: Current perceived cognitive dysfunction was reported by nearly half of respondents (45.7 %), across a wide range of cancer types, with the highest prevalence among survivors of central nervous system cancers. Receiving chemotherapy and current report of depressive symptoms were both strongly associated with current perceived cognitive dysfunction. CONCLUSION: These findings contribute to a growing appreciation of the high prevalence of perceived cognitive dysfunction in survivors of a wide range of cancer types and the potential interactive effect of concurrent symptoms of depression. These findings highlight a need to develop more effective means of preventing or reducing cognitive dysfunction in cancer survivors. IMPLICATIONS FOR CANCER SURVIVORS: Perceived cognitive dysfunction was reported in a wide range of cancer survivors. The potential interactive effect of symptoms of depression suggests the need to develop interventions targeting both cognitive dysfunction and depression to achieve improvements in cognitive functioning.